HISTOPATHOLOGICAL ANALYSIS OF NASAL MASSES IN PATIENTS VISITING A TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL STUDY. - Buriuly, Aman; Luguram Tudu; Besra, Durga Charan; Paswan, Manoj Kumar (Student’s Journal of Health Research Africa, 2024)
Background The prime purpose of this study is to detect the association between clinical signs and cytopathological characteristics, to detect the commonness of several cancerous growths of adenoidal space, and nasal pharynx, and to contrast the cytology of several kinds of nasal polyp. Methods The cross-sectional study was conducted for one year. 150 patients were included in this study and carried out for 1 year. Detailed history of the patients was recorded and cytological examination was done. Results In the age distribution of nasal polyps observed, 21 patients aged 1-10 years, 42 patients aged 11-20 years, 18 patients aged 21-30 years, 23 patients aged 31-40 years, 18 patients aged 41-50 years, 10 patients aged 51-60 years, 17 patients aged 61-70 years, and 1 patient aged 71-80 years were diagnosed with nasal polyps. The gender distribution showed that 88 of the patients were male and 62 were female. Regarding cytopathological characteristics, the surface epithelium was ulcerated in 112 patients, while 38 patients exhibited non-ulcerated surface epithelium. Conclusion In the current research, it is apparent that nasal and paranasal growths comprise a composite of structures that vary from the non – neoplastic reactive conditions to benign and malignant tumors. It is not possible to differentiate simple nasal growth only based on cellular infiltrate. All the cases with nasal growth are under histopathological evaluation because sometimes benign or malignant growths are also present as polyps. Recommendation In any kind of nasal or paranasal growth, histopathological examination is important. Sometimes benign and malignant growths are also present which can be differentiated by histopathological examination.